The gains from cooperative R&D with a concave technology and spillovers - Luca Lambertini; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
We reassess the respective gains from R&D cooperation and competition in a Cournot Duopoly with homogeneous goods, where firms adopt a concave cost-reducing R&D technology. Contrary to the previous literature on the same topic, our main results are that (i) no corner solutions emerge and (ii) cooperation, in the form of either a cartel or a joint venture, is always profitable for firms and (iii) socially superior to independent ventures, provided that spillovers are sufficiently high.
Keywords: 330; Innovationswettbewerb; Forschungskooperation; Duopol; Joint Venture; Technischer Fortschritt; Spillover-Effekt; Theorie